CONTROLLING GREENHOUSE GASES FROM HIGHWAY VEHICLES (Utah Environmental Law Review, 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Programs to reduce emissions of GHGs through increasingly stringent CAFÉ standards are more politically feasible than increasing gasoline taxes or imposing fees on fuel-inefficient vehicles, although a mix of many different measures would probably be the most effective way to reduce GHG emissions. Petroleum demand could be reduced if the cost of driving increased significantly through the use of a carbon tax or by increasing gasoline taxes or by using other economic disincentives. Compared to other developed nations, fuel taxes in the United States are low. State taxes on gasoline averaged 29.7 cents per gallon (cpg) in the last quarter of 2010, and the federal excise tax of 18.4 cpg brings the total tax to 48.1 cpg. State taxes on diesel fuel averaged 28.7 cpg, and the federal tax of 24.4 cpg brings the total to 53.1 cpg. These taxes have been inadequate to maintain the highway system and will become more inadequate if fuel economy increases significantly. Taxes have the advantage of being quick to implement and because of the limited number of refineries the costs of administering the program are low and compliance rates are high. CAFÉ standards have delayed benefits because of the necessity to provide manufacturers with adequate time to meet the standard. Moreover, without high fuel costs, it is difficult to get consumers to buy fuel-efficient vehicles.